2017
DOI: 10.1038/npp.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Withdrawal Drives Anxiety-Related Behaviors by Reducing M-type Potassium Channel Activity in the Lateral Habenula

Abstract: Alcohol use disorders (AUDs) and anxiety disorders (ADs) are often seen concurrently, but their underlying cellular basis is unclear. For unclear reasons, the lateral habenula (LHb), a key brain region involved in the pathophysiology of ADs, becomes hyperactive after ethanol withdrawal. M-type K channels (M-channels), important regulators of neuronal activity, are abundant in the LHb, yet little is known about their role in AUDs and associated ADs. We report here that in rats at 24 h withdrawal from systemic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 77 publications
2
45
2
Order By: Relevance
“…Importantly, LHb hyperactivity facilitates anxiogenesis (Pobbe and Zangrossi, 2008). We recently reported that during withdrawal from repeated cycles of ethanol consumption, rats showed pronounced anxiety-like behaviors (Kang et al, 2017). Therefore, inhibition of LHb CaMKII-AMPAR signaling may also mitigate anxiety-like behaviors in ethanol-withdrawn rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, LHb hyperactivity facilitates anxiogenesis (Pobbe and Zangrossi, 2008). We recently reported that during withdrawal from repeated cycles of ethanol consumption, rats showed pronounced anxiety-like behaviors (Kang et al, 2017). Therefore, inhibition of LHb CaMKII-AMPAR signaling may also mitigate anxiety-like behaviors in ethanol-withdrawn rats.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological recordings were conducted as described (Kang et al, 2017; Zuo et al, 2013). Electrophysiological events were recorded with an Axon 200B amplifier, a Digidata 1440A A/D converter, and Clampfit 10.6 software (Molecular Devices Co., Union City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic exposure to stress leads to a degradation of the LHb, further supporting its role in signaling stress (Jacinto et al 2016). In addition to ethological stressors, the LHb has also been strongly linked with cocaine and ethanol withdrawal stress responses (Neumann et al 2014; Meye et al 2016; Kang et al 2017). Alterations in inhibitory tone in the LHb selectively during drug withdrawal drive negative symptoms and may contribute to continued drug seeking (Meye et al 2016; Kang et al 2017).…”
Section: Lhb Sensitivity To Context and Salient Cuesmentioning
confidence: 99%
“…In addition to ethological stressors, the LHb has also been strongly linked with cocaine and ethanol withdrawal stress responses (Neumann et al 2014; Meye et al 2016; Kang et al 2017). Alterations in inhibitory tone in the LHb selectively during drug withdrawal drive negative symptoms and may contribute to continued drug seeking (Meye et al 2016; Kang et al 2017). How these pathological states alter normal behavioral flexibility processes within the LHb remains unclear.…”
Section: Lhb Sensitivity To Context and Salient Cuesmentioning
confidence: 99%